Determination of trace nitrite in pickled food with a nano-composite electrode by electrodepositing ZnO and Pt nanoparticles on MWCNTs substrate. Issue 2 (December 2015) - Zhang, Man-Le; Huang, Da-Kai; Cao, Zhong; Liu, Ye-Qiu; He, Jing-Lin; Xiong, Jing-Fang; Feng, Ze-Meng; Yin, Yu-Long
Abstract The nitrite in traditional pickled food is potentially harmful to humans. A novel nano-composite of zinc oxide/platinum nanoparticles electrodeposited multiwall carbon nanotubes (MWCNTs) modified glassy carbon electrode (GCE) has been successfully constructed for determination of trace nitrite with high sensitivity. The nano-composite electrode was characterized by scanning electron microscopy and cyclic voltammetry. The effects on pH and loading amounts of MWCNTs, ZnO, and Pt nanoparticles have been investigated to obtain the optimal conditions. A linear relationship was observed between the peak current and nitrite concentration in the range of 4.0 × 10−7∼2.0 × 10−4 mol·L−1, with a detection limit of 8.2 × 10−8 mol·L−1 (S/N = 3). The electrode possessed good selectivity, reproducibility, and stability. It has been applied to the determination of trace nitrite in traditional food samples like pickled vegetable, beef, and chicken with peppers. Finally, a recovery rate was obtained at the range of 96.8–103.8%, showing its quite potential application on food safety inspection.